Carotid Endarterectomy with Contralateral Carotid Occlusion: Is Shunting Necessary? - Ward, Austin; Ferraris, Victor; Saha, Sibu (International Journal of Angiology, 2012)
Background Controversy exists about the effect of contralateral carotid stenosis on the perioperative risks of carotid endarterectomy (CEA). Despite increased perioperative risk, the long-term outcome is improved in patients who undergo ipsilateral CEA with significant contralateral carotid stenosis. Traditionally, this involved shunting the ipsilateral carotid artery during the procedure. It was believed that this minimized the risk for cerebral ischemia. We believe selective shunting can be employed while still avoiding cerebral ischemia. This requires a reliable method of monitoring for ischemia. Intraoperative EEG monitoring has been proven to be a reliable method for monitoring for ischemic changes during a case.Methods A standard operative technique involving continuous EEG monitoring was used. We reviewed the records of carotid endarterectomies in the past 3 years. We present a series of 8 cases of CEA with contralateral occlusion in which shunting was selective based on EEG.Results Of eight patients, seven (87.5%) tolerated the procedure without EEG changes and thus did not requiring intraluminal shunting. There were no long-term complications in our series of patients.Conclusion We found that intraluminal carotid shunting during CEA with contralateral occlusion is not mandatory but neuroprotection methods need to be added to the operative procedure to ensure safety.
Keywords: carotid endarterectomy; cerebral protection; contralateral occlusion; carotid shunting